Association of an Electronic Health Record–Linked Glaucoma Medical Reminder With Patient Satisfaction - Varadaraj, Varshini (JAMA Ophthalmol, 2018)
IMPORTANCE: While dosing reminders for glaucoma medications have been shown to increase drug adherence, an outstanding limitation preventing broad adoption is difficulty linking reminders to medication in each patient’s electronic health record (EHR). OBJECTIVE: To examine the feasibility of implementing an EHR-linked, automated reminder system for glaucoma medications and assess patient satisfaction with it. DESIGN, SETTING, AND PARTICIPANTS: In this prospective, cross-sectional study, patients receiving glaucoma medications were recruited from a university-based glaucoma clinic from April 2017 to January 2018. Analysis began in February 2018. EXPOSURES: A web-based application was added to the EHR patient portal, allowing patients to configure telecommunication-based reminders for their glaucoma medications. For all potential participants, basic information was collected to determine risk of nonadherence with glaucoma medications. Those consenting to participate then answered questions on medication adherence, reminders, and their likelihood of using EHR-linked reminders. They then configured reminders using the EHR patient portal. After 3 months, they answered questions about their satisfaction with the system. MAIN OUTCOMES AND MEASURES: Proportions of patients and high-risk patients willing to use the reminders, and patient satisfaction with the system. RESULTS: Of 147 patients approached, 100 (68%) agreed to participate, of whom the majority were men (54 [54%]) and white (51 [51%]), with a mean (SD) age of 65 (12.4) years. There were no differences between those willing and unwilling to participate, except for a slightly lower self-reported medication adherence rate among those who participated (mean [SD], 91% [13.6%] vs 97% [6.0%]). Based on a previously validated risk assessment score, 9% (9 of 100) of participants were categorized as being at high risk for poor adherence (≥50% probability of nonadherence) compared with 11% (5 of 47) of nonparticipants. Of 100 participants, 94 ultimately configured reminders, of whom 89 (95%) completed follow-up. On follow-up, 74% (n = 66; 95% CI, 65-83) of participants found the reminders to be useful, 15% (n = 13) were neutral, and 11% (n = 10) found them not useful. Most participants (72 [81%]; 95% CI, 77-85) had help configuring reminders. CONCLUSIONS AND RELEVANCE: Electronic health records–linked reminders had good uptake and were well received among patients at a tertiary glaucoma clinic. These portals may represent a new and convenient method of allowing patients to link their glaucoma medications to automated reminders, although the generalizability of these results and the effect on glaucoma outcomes remains unknown.